Zwischen Akzeptanz und Resignation Die Funktionen des sozialrechtlichen Vorverfahrens aus Sicht der Widerspruchsführenden am Beispiel der Deutschen Rentenversicherung Bund - Schubert, Nina (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2022)
Anyone seeking legal protection in social law cannot avoid the opposition procedure. But does the preliminary procedure merely serve as a conduiter on the way to court? Or does it fulfill its intended function and pacify the parties involved? This work answers these questions on the basis of specially collected empirical findings. For the first time, the study provides insight into the appraisal of the procedure by the appellants and examines the theoretical expectations of the acceptance function of the opposition procedure.